O espaço urbano como construção poética do sujeito - Susanna Busato (Estudos de Literatura Brasileira Contemporânea)
This is a critical and analytical study about some poems written by the Brazilianpoet Fábio Weintraub concerning the construction of the poeticspace as acritical and poetical view of the subject. The lyric aspect in the poet’s work is objective and sensitive towards urban scenes in which all the objects play a role as images of the cities’ routine, in which space is performed as the drama of thesubject who sees the scene.